2014
DOI: 10.1111/dom.12261
|View full text |Cite
|
Sign up to set email alerts
|

Modeling effects of SGLT‐2 inhibitor dapagliflozin treatment versus standard diabetes therapy on cardiovascular and microvascular outcomes

Abstract: On the basis of simulation results, adding dapagliflozin to currently available treatment options is projected to further decrease the CV and microvascular complications associated with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 32 publications
1
61
0
1
Order By: Relevance
“…Another recent meta-analysis has reported similar potential beneficial effect on CV outcomes of all SGLT2-I considered [61]. A simulated projection by using the Archimedes model showed that adding dapagliflozin to other antidiabetic agents further decreases CV and microvascular complications associated with T2DM over a 20-year period [62]. Thus, dapagliflozin has the potential for a beneficial effect both in the overall population and in those with a history of CV disease [8].…”
Section: Dapagliflozin and CV Riskmentioning
confidence: 88%
“…Another recent meta-analysis has reported similar potential beneficial effect on CV outcomes of all SGLT2-I considered [61]. A simulated projection by using the Archimedes model showed that adding dapagliflozin to other antidiabetic agents further decreases CV and microvascular complications associated with T2DM over a 20-year period [62]. Thus, dapagliflozin has the potential for a beneficial effect both in the overall population and in those with a history of CV disease [8].…”
Section: Dapagliflozin and CV Riskmentioning
confidence: 88%
“…Recently, one study used the Archimedes Model to predict 20-year outcomes and found significant reductions in the risk of MI, stroke, CV death and all causes of death with SGLT2i treatment versus standard care. 166 Nevertheless, to confirm these results, several trials are now in progress in order to evaluate the CV safety of the other SGLT-2i. 150 The Multicenter Trial to Evaluate the Effect of Dapagliflozin on the Incidence of Cardiovascular Events (DECLARE-TIMI58), expected to be finished in 2019, was designed to evaluate the effect of dapagliflozin on the incidence of CV events.…”
Section: Cardiovascular Safety Of Sglt-2i: Evidence From Studiesmentioning
confidence: 97%
“…However, a recent study on dapagliflozin proposed that SGLT-2 inhibitors may possess an additional diuretic-like capacity to lower blood pressure [173]. The improvements in blood pressure, associated to a moderate decrease in body weight [174] induced by treatment with SGLT-2 inhibitors suggest the potential for reducing the risk of cardiovascular events [175,176]. To date, SGLT-2 inhibitors are generally well tolerated, with a favorable safety profile similar to that of placebo.…”
Section: How Conventional Diabetic Treatments May Ameliorate Endothelmentioning
confidence: 99%
“…The epigallocatechin-3-gallate (EGCG), the most abundant active polyphenolic component of green tea, is capable of inhibiting NLRP3 inflammasome via enhancing the Nrf2 antioxidant pathway [184]. Moreover, the protective effects of astragaloside IV and cycloastragenol -both contained in Astragalus membranaceus Moench (Fabaceae) -against endoplasmic reticulum stress-induced apoptosis are thought to be mediated via NLRP3 inflammasome inhibition in endothelial cells [176,185]. NLRP3 inflammasome inhibition has also been proposed as new pivotal mechanism contributing to endothelial protective function of rutin, a flavonoid that can be obtained from different dietary sources [186].…”
Section: New Strategies For Treatment Of Diabetes and Their Impact Onmentioning
confidence: 99%